Hotel Portofino. Season three [videorecording (DVD)] - Baker, Matt (Screenwriter) (PBS Distribution, 2024)
Bella is preparing for her father and sister's arrival but is thrown when Cecil appears requesting divorce. Over the weeks, Bella must decide her future as well as avoiding fascist leader Danioni. But with the Wall Street Crash, things get worse as Bella and Cecil lose everything.